Implementasi Homeschooling Komunitas dalam Upaya Meningkatkan Kecerdasan Sosial pada Siswa Kesetaraan Paket A di Homeschooling Pena Surabaya - Febrianti, Sherly Purnama; Widodo, Widodo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
Humans are social creatures who live in need of other people. Social intelligence concerns how students communicate, behave, socialize with other people and the surrounding environment. Social intelligence includes five aspects including 1) situational awareness or situational awareness is the ability to understand, be sensitive and care about the surrounding environmental conditions, 2) presence or self-carrying ability is the ability to be ethical both in appearance or communication, 3) authenticity or authenticity is behavior possessed by students so that other people can judge it, 4) clarity or clarity is the ability possessed by students in expressing their opinions so that other people can know the intentions and goals conveyed by these students and 5) empathy or empathy is the ability to understand conditions and other people's feelings. The purposes of this study are 1) to describe the implementation of community homeschooling in efforts to increase social intelligence, 2) supporting factors and 3) inhibiting factors in increasing social intelligence in package A equivalency students at Pena Homeschooling Surabaya. The method used is descriptive qualitative using in-depth interview techniques, observation and documentation.